2007
DOI: 10.1530/eje-07-0193
|View full text |Cite
|
Sign up to set email alerts
|

Reduced 11β-hydroxysteroid dehydrogenase type 1 activity in obese boys

Abstract: Objective: The incidence of childhood obesity and type 2 diabetes has reached epidemic proportions. Glucocorticoid excess causes central obesity and diabetes mellitus as seen in Cushing's syndrome. The 11b-hydroxysteroid dehydrogenase type 1 enzyme (11b-HSD1) regenerates active cortisol from inactive cortisone. Altered 11b-HSD1 may cause tissue-specific Cushing's syndrome with central obesity and impaired glucose homeostasis. Design, patients, and methods: Clinical and laboratory characteristics, and anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Lower hepatic 11b-HSD1 activity (assessed by the urinary tetrahydrocortisol þ 5a-tetrahydrocortisol/tetrahydrocortisone ratio) has been reported in obese children 28 and is supported by the finding that the activation of oral cortisone to cortisol is impaired in obesity. 5 However, there is no consensus on plasma cortisol levels in obese subjects.…”
Section: Discussionmentioning
confidence: 70%
“…Lower hepatic 11b-HSD1 activity (assessed by the urinary tetrahydrocortisol þ 5a-tetrahydrocortisol/tetrahydrocortisone ratio) has been reported in obese children 28 and is supported by the finding that the activation of oral cortisone to cortisol is impaired in obesity. 5 However, there is no consensus on plasma cortisol levels in obese subjects.…”
Section: Discussionmentioning
confidence: 70%
“…This process may be of particular relevance in central obesity due to 11␤-HSD1 activity in the omental fat tissue (32). However, Wiegand et al (33) reported that 11␤-HSD1 activity is reduced in obese boys. In our study, we did not find a significant relationship between waist circumference and cortisol or cortisone.…”
Section: Discussionmentioning
confidence: 99%
“…Wiegand et al[ 14] studied 11β-HSD1 activity and total cortisol metabolite excretion in obese children aged 12–18 years. 11β-HSD1 activity and total cortisol metabolite excretion showed no correlation with waist–hip ratio, fat mass (percentage of body mass), or the homeostasis model assessment of insulin resistance index.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that 11β-HSD1 activity increases with age, and is reduced in obese boys. In addition, obese children had a higher total cortisol metabolite excretion suggesting increased activation of the hypothalamic-pituitary-adrenal axis [14]. Lean adult women have lower 11β-HSD1 gene expression in SC compared with men, whereas no significant difference was found between obese men and women.…”
Section: Discussionmentioning
confidence: 99%